Addressing Portal Hypertension: Exploring the Crucial Role of Partial Splenic Embolization in Critical Situations - Suwanto, Agnes Wanda; Amalia, Fini; NA, Achmad Bayhaqi (International Journal of Radiology and Imaging, 2023)
Background: Esophageal varices are one of the most common symptoms of direct outcomes of portal hypertension besides ascites, hepatorenal syndrome, and hypersplenism. Nonselective beta-blockers or band ligation are currently the effective primary preventive options for variceal hemorrhage. The use of partial splenic arterial embolization for the management of variceal hemorrhage in patients with portal hypertension has been described in a small number of reports. Case Report: A girl, 6 y.o., was hospitalized with hematemesis with hypovolemic shock. Laboratory findings show anemia and thrombocytopenia. Radiology and endoscopy show grade III esophageal varices with hepatosplenomegaly. Because of the high risk of morbidity in surgical procedures, partial splenic embolization was performed to treat portal hypertension. Discussion: The combination of varices and a low platelet count puts these patients at high risk for catastrophic hemorrhage. Partial splenic embolization reduces splenic blood volume, resulting in a decrease in venous drainage and a reduction in portal venous flow and pressure. Conclusion: The use of partial splenic arterial embolization to manage variceal hemorrhage in patients with portal hypertension has been described. Embolization can be used alone or in combination with other therapies, like endoscopic ligation or retrograde transvenous variceal obliteration, to treat a variety of conditions. Keywords: Embolization, esophageal varices, splenomegaly, portal hypertension